Equality in Islam: Prophetic Traditions, Islamic Educational Perspectives, and Multicultural Democracy in Southeast Asia - Alwy Ahmed Mohamed; Muhammad K. Ridwan; Qudra Bezibweki; Muthoifin (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: Examining the conflict between traditional interpretations and modern readings, this study explores how Islamic doctrines and prophetic traditions influence Southeast Asian Muslim communities' conceptions of equality. The goal is to examine how social, economic, and gender equality are framed in pluralistic cultural contexts using Hadith and Qur'anic teaching. Theoretical framework: The study is grounded in Islamic jurisprudence, ethics, and social theory, exploring how classical sources interact with modern interpretations to inform notions of justice, human dignity, and communal harmony. The framework situates these interpretations within ongoing debates about tradition, reform, and socio-religious adaptation in Southeast Asia. Literature review: While modern scholarship increasingly focuses on gender justice, economic justice, and interreligious tolerance, earlier research emphasizes the emphasis of ancient Islamic scriptures on spiritual and community equality.  This study fills a gap in the literature by combining field observations and textual analysis in a Southeast Asian environment. Method: This study employs a qualitative, field-based methodology that combines interviews with Islamic scholars, educators, and community leaders with observations made in madrasahs, pesantrens, and places of worship. Results: The results show that Muslims in Southeast Asia are actively discussing what equality means, striking a balance between modern social realities and devotion to traditional prophetic traditions.  While traditional readings continue to influence cultural and spiritual standards, contemporary reinterpretations highlight gender justice, economic parity, and interreligious tolerance as key topics. Implications: In order to promote more inclusive and egalitarian Muslim societies, the study emphasizes the possibilities of fusing classic Islamic sources with contemporary social imperatives. The findings of this study can help religious leaders, educators, and legislators advance social justice and human dignity. Novelty: The comparative, field-based methodology of the study, which combines Hadith analysis, Islamic theory, and empirical observations in Southeast Asia, is innovative. It offers a practical framework for comprehending equality in modern Muslim situations.